Water quality of surface runoff in loop two catchment area in UKM - Norshahkilla Izzatul Zaiedy,; Othman A. Karim,; Nurul Afina Abd Mutalib, (Penerbit Universiti Kebangsaan Malaysia, 2016)
For a country that is developing, there is a need to control and maintain the quality of raw water, with adequate quantities to ensure continuous supply of clean water. In Malaysia, urban development activities especially constructions, is believed to be one of the activities that contributes to the deterioration of the quality of surface runoff. The main objectives of this project are to investigate water quality of surface water runoff at UKM’s loop two catchment areas and to observe the effect of slope failure, erosion, and construction activities on surface water quality in UKM Bangi campus. Besides that, the development of hydraulic models using HEC-RAS software is also the objective of this research. This research is conducted through field study and laboratory works. The main findings confirmed that water quality and total surface runoff in the catchment is directly affected by slope failure, erosion, and construction activities. Results from HEC-RAS modeling revealed that the drains surrounding the lake are not overflowing or flooding.